Multivariate analysis of poor outcome after anterior surgery in multilevel cervical spondylotic myelopathy patients with heterotopic ossification and preoperative kyphotic alignment - Li S; Zhang B; Shen Y; Wu Z (Dove Medical Press, 2019)
ShaoQing Li,1 BaoYang Zhang,2 Yong Shen,2 ZhanYong Wu11Department of Orthopedic Surgery, The Orthopedics Hospital of XingTai City, XingTai 054000, People’s Republic of China; 2Department of Orthopedic Surgery, The Third Hospital of Hebei Medical University, Shijiazhuang 050051, People’s Republic of ChinaCorrespondence: ZhanYong WuDepartment of Orthopedic Surgery, The Orthopedics Hospital of XingTai City, No. 202 Bayi Road, XingTai 054000, People’s Republic of ChinaTel +86 1 863 116 4033Fax +86 0 319 206 9476Email xkzyywsj@163.comObjective: The aim of this study was to evaluate the risk factors for poor outcome in patients who underwent multi-segmental anterior surgery, and analyze postoperative complications.Methods: We retrospectively reviewed 158 patients after anterior surgery due to multilevel cervical spondylotic myelopathy (m-CSM) between June 2008 and June 2016. Adjusted ORs and 95% CIs were determined by multivariate logistic regression analysis. Cutoff values and the area under the curve for continuous risk factors were calculated through receiver operating characteristic curve analysis. The chi-squared test was performed for the comparison of complications among the three surgical groups.Results: By analyzing 105 patients with good outcome and 53 patients with poor outcome, we established that the risk factors for poor outcome were advanced age (OR =1.12, P=0.003), longer duration of symptoms (OR =1.07, P=0.028), and bigger kyphotic angle at final follow-up (OR =1.29, P< 0.001). The optimal cutoff values for age, duration of symptoms, and kyphotic angle at final follow-up were 63.1 years, 15.5 months, and 5.3 angle. Postoperative complications occurred in 21 patients (13.3%). The incidence of dysphagia and cerebrospinal ﬂuid leakage were higher in multilevel anterior cervical discectomy and fusion (m-ACDF) group than in other groups (P< 0.05).Conclusion: Advanced age, longer duration of symptoms, and bigger kyphotic angle at final follow-up were the risk factors for poor postoperative outcome in patients with m-CSM. The complications after hybrid approach and m-ACDF approach were less than after anterior cervical corpectomy and fusion approach.Keywords: multilevel cervical spondylotic myelopathy, kyphotic, heterotopic ossification, hybrid approach, complication